Effectiveness of Mindfulness-Based Cognitive Therapy for Improving Subjective and Eudaimonic Well-Being in Healthy Individuals: A Randomized Controlled Trial - Kosugi, Teppei; Ninomiya, Akira; Nagaoka, Maki; Hashimoto, Zenta; Sawada, Kyosuke; Park, Sunre; Fujisawa, Daisuke; Mimura, Masaru; Sado, Mitsuhiro (Frontiers in Psychology, 2021)
Objectives Better subjective and eudaimonic well-being fosters better health conditions. Several studies have confirmed that mindfulness-based interventions are effective for improving well-being; however, the samples examined in these studies have been limited to specific populations, and the studies only measured certain aspects of well-being rather than the entire construct. Additionally, few studies have examined the effect of mindfulness-based cognitive therapy on subjective well-being. The present study examines the feasibility of mindfulness-based cognitive therapy and its effectiveness for improving subjective and eudaimonic well-being among community residents. Methods The study design featured an eight-week randomized, waiting-list controlled, parallel-group study. Eight weekly mindfulness classes, followed by two monthly classes, were provided for healthy individuals aged 20–65 years who had a Satisfaction with Life Scale score of less than 25. This trial was registered with the University Hospital Medical Information Network Clinical Trials Registry (ID: UMIN000031885, URL: https://upload.umin.ac.jp/cgi-open-bin/ctr_e/ctr_view.cgi?recptno=R000036376) Results The results showed that life evaluation and mindfulness skills were significantly improved at eight weeks, and this effect was maintained up to the end of the follow-up period. Positive affect and the eudaimonic well-being were significantly improved at 16 weeks. Conclusions Eight weeks of MBCT with a two-month follow-up period improves cognitive and affective aspects of subjective and eudaimonic well-being in healthy individuals. The order of improvement was cognitive, positive affective, and eudaimonic. To verify these findings, multi-center randomized controlled trials with active control groups and longer follow-up periods are warranted.